Pengembangan E-Modul Berbasis Google Sites Terintegrasi Educandy Mata Pelajaran Pendidikan Pancasila Materi Kita Beragam Tetapi Tetap Satu Kelas II SDN Bangilan Bojonegoro - Nia Rohmatul Fadhilah; Midya Yuli Amreta; Muhammad Romadlon Habibullah (Journal of Practice Learning and Educational Development, 2026)
Digital technology offers significant opportunities in education through interactive learning media development. At SDN Bangilan Bojonegoro, Pancasila Education teaching remains conventional and monotonous, causing student disengagement and boredom. Teachers haven't utilized technology to create varied, engaging, and interactive materials. This study aimed to help second-grade students at SDN Bangilan understand diverse yet unified Pancasila Education content using a Google Sites-based e-module integrated with Educandy. The research employed Research and Development (R&D) methodology with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The study involved 13 second-grade students. Data collection included observations, interviews, documentation, and validation surveys from media experts, subject experts, and student trials (small and large scale). Validation results showed the e-module achieved "highly suitable" status for learning implementation. Content validation scored 96%, media 92%, and language 92%. Student response questionnaires rated it as "very interesting" and "very helpful" with a 98% average score. Therefore, the Google Sites-based e-module integrated with Educandy proves suitable as an innovative, interactive learning medium for elementary school Pancasila Education, effectively addressing conventional teaching limitations and enhancing student engagement.